Análise da capacidade de uso da terra na bacia hidrográfica do Riacho Chafariz com auxílio de geotecnologias - Nascimento, José Jerônimo de Souza (2020)
Territorial occupations have always been related to the natural resources available, especially soil, which are used by agricultural activities. However, these actions, can have negative consequences for these resources, it will depending on the way they occur. Despite the important advances in technological means, it is still challenging to put into practice an efficient sustainable management of soil. It is necessary an adequate planning that contemplates its potentialities and limitations. In this perspective, the general objective of the research was to analyze the soil use capacity of the hydrographic basin of Riacho Chafariz (HBRC), Borborema Geographical Mesoregion, State of Paraíba, Brazil. For this, factors such as slope and soil types were evaluated, which are contained in the Guide for Utility Survey of the Physical Environment and Soil Classification in the Capacity Use System (CUS). Thus, it was used for the production of thematic maps, the technique of geoprocessing and overlaying maps (overlay). The results showed that in HBRC the altitudes vary between 296m and 872 m, the slope has the following classes with greater representation: flat (30.6%), smoothly wavy (33.4%) and wavy (19.2%). The types of soils found are LUVISSOLOS, LATOSSOLOS and NEOSSOLOS. Thus, six classes of soil use capacity were identified at HBRC, with Class VI predominating (Soils with permanent limitations and / or risk of severe degradation) with 40.9% of the HBRC area. The Class I (Soil without or with slight permanent limitations) with only 13.6%. Finally, according to the adopted criteria, it is considered that HBRC have most of its soil with inadequate use for productive capacity